The Community Structure of Gastropods (Mollusca Phylum) in The Intertidal Zone of Saung Beach, Wakan Village, Jerowaru District, East Lombok Regency - Suganda, M. Tomy Aria; Karnan, Karnan; Ilhamdi, Moh. Liwa (Jurnal Biologi Tropis, 2024)
Gastropods are one of the phylum Mollusca classes having a single shell, normally spiral-shaped. This research aimed to analyze the Gastropod community structure (Mollusca Phylum) in the Intertidal Zone of Wakan Village, Jerowaru District, East Lombok Regency. The combination of line and quadrat transect was implemented to take samples in this study. The variables in the research include the type and quantity of Gastropods. There were 1.715 individual of Gastropod found in this study. They were included in 11 families and 17 species. The Gastropod species with the highest abundance value in station I and II was Strombus urceus with the abundance value of 12,8 ind/m2 and 5,72 ind/m2, respectively. Meanwhile, in station III, it was Terebralia sulcate with the abundance value of 3,4 ind/m2. The diversity index of Gastropods in the research location was categorized as medium (H’=2,32) with a stable divercity index (E=0,84) and a low domination index (C=0,14).